Eliciting community preferences for complementary micro health insurance: a discrete choice experiment in rural Malawi - Abiiro, Gilbert Abotisem; De Allegri, Manuela (Social science & medicine, 2014)
There is a limited understanding of preferences for micro health insurance (MHI) as a strategy for moving towards universal health coverage. Using a discrete choice experiment (DCE), we explored community preferences for the attributes and attribute-levels of a prospective MHI scheme, aimed at filling health coverage gaps in Malawi. Through a qualitative study informed by a literature review, we identified six MHI attributes (and attribute-levels): unit of enrollment, management structure, health service benefit package, copayment levels, transportation coverage, and monthly premium per person. Qualitative data was collected from 12 focus group discussions and 8 interviews in August-September, 2012. We constructed a D-efficient design of eighteen choice-sets, each comprising two MHI choice alternatives and an opt-out. Using pictorial images, trained interviewers administered the DCE in March-May, 2013, to 814 household heads and/or their spouse(s) in two rural districts. We estimated preferences for attribute-levels and relative importance of attributes using conditional and nested logit models. The results showed that all attribute-levels except management by external NGO significantly influenced respondents' choice behavior (P < 0.05). These included: enrollment as core nuclear family (odds ratio (OR) = 1.1574), extended family (OR = 1.1132), compared to individual; management by community committee (OR = 0.9494) compared to local micro finance institution; comprehensive health service package (OR = 1.4621), medium service package (OR = 1.2761), compared to basic service package; no copayment (OR = 1.1347), 25% copayment (OR = 1.1090), compared to 50% copayment; coverage of all transport (OR = 1.5841), referral and emergency transport (OR = 1.2610), compared to no transport; and premium (OR = 0.9994). The relative importance of attributes is ordered as: transport, health services benefits, enrollment unit, premium, copayment, and management. To maximize consumer utility and encourage community acceptance of MHI, potential MHI schemes should cover transport costs, offer a comprehensive benefit package, define the core family as the unit of enrollment, avoid high copayments, and be managed by a competent financial institution.